PERSEPSI SISWA TERHADAP PEMBELAJARAN MATEMATIKA SECARA DARING DENGAN MENGGUNAKAN LMS MOODLE SELAMA PANDEMI COVID-19 - Edi Supriyadi; Dadang Juandi (IKIP Siliwangi, 2022)
The significant influence of the Covid-19 pandemic on the education sector has changed the learning process from face-to-face to online learning. One of the tools used in optimizing the online learning process is the Moodle Learning Management System (LMS). Students' perception of moodle becomes data that is analyzed and interpreted during online learning of mathematics. There are 18 question items distributed via google form using a semantic differential scale of 1-7. Several aspects are examined from the questionnaire, including affective, cognitive and behavioural elements to students in SMP X, data analysis technique by calculating the average of each statement item with the criteria of an average score of <5 Negative response and an average score of 5 then the indicator has a positive response. In addition, the total percentage of students who fill out each indicator is also analyzed to compare the proportions. The data obtained from this study include the affective element of students choosing the benefits of LMS Moodle on a scale of 5-7 by 76%. From the cognitive element of students' perceptions, from 5-7, as many as 68% of students were motivated to learn to use the Moodle LMS during the Covid-19 pandemic. And from the behavioural aspect, 82% of students choose from a scale of 5-7 they choose the emergence of learning independence when using this Moodle LMS.